Driver and barrier of purchase intention on group buying app - Jianhua, Chu; Ali, Mass Hareeza; Mohd Said, Ridzwana (Elite Scientific Publications, 2024)
The global group-buying app usage rate has dramatically increased in mobile phone-based marketing. Because of its economic value and social benefits, many enterprises regard group buying apps as an essential online marketing and brand-building channel. Therefore, studying consumers’ purchase intention on group buying apps has become an important topic to promote the development of online marketing. This research investigates the relationship among perceived value, customer engagement, and purchase intention by integrating the Cognition-Affection-Conation model, perceived value theory, and regulatory focus theory. Furthermore, this study studies the mediating impact of customer engagement and the moderating influence of regulatory focus. Distribute and collect 562 validated questionnaires from online Chinese millennials (born between 1981 and 1996) who had used group-buying apps in the past six months and used purpose-based sampling technology to collect data in China. Here, partial least squares and structural equation modeling (PLS-SEM) test the hypothesis through data analysis and draw the conclusion. This study’s conclusions included three significant discoveries. Firstly, perceived benefit, sacrifice, and customer engagement positively impacted the purchase intention of the group-buying app. Secondly, the findings showed that the relationship between perceived values and purchase intention was mediated by customer engagement, which exhibited the most decisive influence. Thirdly, the moderation analysis revealed that promotion focus positively influenced perceived values and customer engagement.